«Rechtsstaat oder diktatur?» Hermann Heller in face of fascism: Peer-reviewed article (Italian Review of Legal History, 2023)
This issue investigates Hermann Heller’s analysis of the legal-philosophical and political-social features of Italian fascism, summarized in his in-depth work Europa und der Fascismus. More specifically, this German jurist, involved in first person in the composite and controversial framework of the Weimar Republic, had showed a keen interest in fascist phenomenon very soon. This essay, based on the ferocious criticism of legal positivism and philosophical irrationalism, was particularly interesting because Heller was not a conservative scholar but a social-democratic thinker, even if his conception of socialism was unusual because he rejected the two main postulates of the political program of German Social Democratic Party: internationalism and dialectical materialism. The originality of Heller’s criticism to Italian fascism lies in his ability to have understood, in unsuspected times, that fascist ideology was not based on a well-articulated political program but a jumble of utterly heterogeneous, in the name of a kind of intuitive relativism.
Keywords: Hermann Heller; anti-democratic systems; rule of law; legal positivism; corporatism